2002
DOI: 10.1007/s00784-001-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological results of sensory recovery after radial forearm flap transfer

Abstract: The necessity of nerve anastomosis in an attempt to regain dermal sensitivity following pedicled or free-flap transfer has been the basis of many discussions. In our study, we investigated the degree of sensory recovery with emphasis on the different nerval qualities, on the radial forearm flap and correlated it to the histological and immunohistological findings. Nineteen patients with radial forearm free flap -five of whom underwent nerve anastomosis -were examined. The follow-up interval was 20.3 months (av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most of the previous studies that compared spontaneous sensory recovery and recovery after nerve coaptation yielded controversial results. Certain studies showed a benefit in sensory recovery after nerve coaptation, whereas others reported satisfactory spontaneous reinnervation from the surrounding skin (Ayhan Oral, Zeynep Sevim, Gorgu, & Yucel Oztan, ; Schultes, Gaggl, & Karcher, ; Vesper, Heiland, Blake, Flinzberg, & Schmelzle, ; Vesper, Heiland, Flinzberg, & Schmelzle, ). Furthermore, a comparison of the existing literature is difficult as different examination modalities and times were employed (Beugels et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies that compared spontaneous sensory recovery and recovery after nerve coaptation yielded controversial results. Certain studies showed a benefit in sensory recovery after nerve coaptation, whereas others reported satisfactory spontaneous reinnervation from the surrounding skin (Ayhan Oral, Zeynep Sevim, Gorgu, & Yucel Oztan, ; Schultes, Gaggl, & Karcher, ; Vesper, Heiland, Blake, Flinzberg, & Schmelzle, ; Vesper, Heiland, Flinzberg, & Schmelzle, ). Furthermore, a comparison of the existing literature is difficult as different examination modalities and times were employed (Beugels et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…10 In contrast, in oral cavity reconstruction using radial forearm flaps and latissimus dorsi flaps, sensory reinnervation has been shown in neurotized and nonneurotized flaps [19][20][21] with some authors reporting no superior improvement in flaps with nerval reconstruction. 19,20 Moreover, satisfactory partial sensory reinnervation has also been described in nonneurotized free flaps in breast reconstruction. [6][7][8][9]11,12,15,[22][23][24][25][26] In addition, studies investigating sensory recovery after free flap surgery are difficult to compare as modalities and interpretation of sensory outcomes are unstandardized and vary widely.…”
mentioning
confidence: 99%
“…7–9,11–16 Similarly, in extremity reconstruction, previous studies describe overall diminished sensory recovery gradually improving over time 2,10,17,18 and faster recovery in neurotized flaps. 10 In contrast, in oral cavity reconstruction using radial forearm flaps and latissimus dorsi flaps, sensory reinnervation has been shown in neurotized and nonneurotized flaps 19–21 with some authors reporting no superior improvement in flaps with nerval reconstruction. 19,20 Moreover, satisfactory partial sensory reinnervation has also been described in nonneurotized free flaps in breast reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to point out that when performing a free gracilis for lip reconstruction, we always consider whether it is feasible to add the Pribaz facial artery musculomucosal (FAMM) flap 31 and sensory innervation to restore sensation at the reconstructed lip. 32,33 A FAMM flap at the resection step of the procedure can be prepared; it provides inner mucosa coverage of the new lip and the vermilion. The FAMM flap, according to Pribaz, can be inferiorly or superiorly based.…”
Section: Surgical Techniquementioning
confidence: 99%